Analisa Kualitas Madu Singkong (Gula Pereduksi, Kadar Air, dan Total Padatan Terlarut) Pasca Proses Pengolahan dengan Vacuum Cooling - A. Lastriyanto; A. I. Aulia (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
Honey is a natural liquid that is commonly used as an addition to food or drinks and has properties thatare believed to increase endurance and cure various diseases. Honey has different characteristics basedon taste, aroma, color. This can not be separated from the physico-chemical content of honey. Highwater content in honey can reduce the shelf life of honey because it can cause fermentation by yeast.So, in this study, cassava honey was processed using a vacuum cooling device designed by Mr. AnangLastriyanto from Brawijaya University with the aim of seeing the effect of changes in honey quality onlow temperature heating with vacuum pressure to reduce the water content of honey. After processingwith a vacuum cooling device, the reducing sugar content, moisture content and total dissolved solidsin the cassava honey are tested to show the effect of using a vacuum cooling device. Real honey has areducing sugar content of 52.43% and after vacuum cooling it becomes 55.06%. The water content ofreal honey is 27.2% to 11.22 after the vacuum cooling process. The total dissolved solids of the originalhoney was 68.75% Brix to 79.5% Brix after vacuum cooling.